Incidence of BK Virus Nephropathy (BKVN) in Renal Transplant Recipients - Pezeshgi, A. (Avicenna Organ Transplantation Institute, 2012)
Background: BK virus nephropathy (BKVN) is one of the complications of renal transplantation that causes graft loss in renal transplant recipients. Objective: To determine the incidence of BKVN after renal transplantation in Hasheminejad Hospital, Tehran, Iran. Methods: In this analytical cross-sectional study, we evaluated 31 consecutive kidney transplant recipients (21 men and 10 women) for BK and JC viral infections and BKVN during one year after transplantation, Urine of patients was tested for the presence of decoy cells and DNA of BK and JC virus by PCR. The serum load of BK and JC virus was assessed in patients 3, 6, 9, and 12 months after transplantation. Renal biopsy was performed in presence of allograft dysfunction or viral load >10(7) copies/mL. Results: The prevalences of decoy cells and BK and JC viral DNA in urine of patients were 16%, 29%, and 23%, respectively. BK or JC virus was found in 45% of the urine samples. During one year follow-up, no cases of BKVN was observed. Conclusion: Despite a high rate of BK viral infection, no one with BKVN was observed in our kidney transplant recipients. Therefore, screening of all transplant recipients for BKVN is not recommended.